Programmable ZnO nanowire transistors using switchable polarization of ferroelectric liquid crystal - Hong, W; Sohn, J; Cha, S; Kim, J; Park, J; Choi, S; Coles, H; Welland, M (2013)
We demonstrate modulations of electrical conductance and hysteresis behavior in ZnO nanowire transistors via electrically polarized switching of ferroelectric liquid crystal (FLC). After coating a nanowire channel in the transistors with FLCs, we observed large increases in channel conductance and hysteresis width, and a strong dependence of hysteresis loops on the polarization states associated with the orientation of electric dipole moments along the direction of the gate electric field. Furthermore, the reversible switching and retention characteristics provide the feasibility of creating a hybrid system with switch and memory functions. © 2013 American Institute of Physics.